2011
DOI: 10.1302/0301-620x.93b1.25498
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic pulmonary embolism after outpatient arthroscopic procedures of the knee

Abstract: Pulmonary embolism is a serious complication after arthroscopy of the knee, about which there is limited information. We have identified the incidence and risk factors for symptomatic pulmonary embolism after arthroscopic procedures on outpatients. The New York State Department of Health Statewide Planning and Research Cooperative System database was used to review arthroscopic procedures of the knee performed on outpatients between 1997 and 2006, and identify those admitted within 90 days of surgery with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 25 publications
(25 reference statements)
4
47
1
1
Order By: Relevance
“…This statistical approach has made our findings robust to type I and II errors, although a methodological concern may be selection bias as only patients undergoing minor elective procedures were included. On the other hand, available epidemiological data obtained from over 400,000 knee arthroscopies (by far the most common procedure in this study) suggest that such patients reflect the general population, for example with regard to history of cancer and comorbidities [38]. In addition, the standardized sampling conditions in our operating rooms are likely to have benefitted the reliability of intersubject MA metabolite concentration comparisons.…”
Section: Discussionmentioning
confidence: 85%
“…This statistical approach has made our findings robust to type I and II errors, although a methodological concern may be selection bias as only patients undergoing minor elective procedures were included. On the other hand, available epidemiological data obtained from over 400,000 knee arthroscopies (by far the most common procedure in this study) suggest that such patients reflect the general population, for example with regard to history of cancer and comorbidities [38]. In addition, the standardized sampling conditions in our operating rooms are likely to have benefitted the reliability of intersubject MA metabolite concentration comparisons.…”
Section: Discussionmentioning
confidence: 85%
“…In a series of 85 patients who underwent knee arthroscopy, Williams et al [53] found that 8.6% of the patients who possessed at least one classic risk factor were diagnosed with a clinically silent DVT compared with a rate of 1.6% in those who possessed no risk factors. Age has notably been documented as a risk factor for VTE after knee arthroscopy [16,29]; however, with the younger age at which trauma such as knee dislocations usually occurs, it is difficult to assess how this affects the risk of VTE in the multiligamentous knee reconstruction population. To reiterate, given the lack of symptomatic VTE diagnosed in our series, further statistical analysis of the risk factors mentioned here was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…As such, these patients are at risk of developing venous thromboembolism (VTE). Numerous reports have documented the frequency of and risk factors for developing a VTE after hip and knee arthroplasty, knee arthroscopy, lower extremity trauma, and even hip arthroscopy [2,3,5,7,16,17,29,35,41,43,45,47]. However, data with regard to VTE after multiligamentous knee reconstruction are scarce [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hetsroni et al . found that the risk of developing a PE increased to more than six fold for patients over 40 years compared to less than 20 years, and that procedures taking longer than 90 minutes increased the risk of PE by a factor of three compared to surgeries taking less than 30 minutes 6. Prevention of DVTs following this commonly performed surgery can not only lead to postoperative morbidity and mortality, but also reduced hospital stays and healthcare costs 1318…”
Section: Discussionmentioning
confidence: 99%
“…As a result, controversy has surrounded the use of thromboprophylaxis in routine arthroscopy of the knee. Current literature, however, reports an incidence of deep vein thrombosis (DVT) of 9.9% overall and 2.1% for proximal DVTs,5 and a pulmonary embolism (PE) rate of 0.028%6 in patients undergoing routine knee arthroscopy.…”
Section: Introductionmentioning
confidence: 99%